2017
DOI: 10.1590/1678-4766e2017123
|View full text |Cite
|
Sign up to set email alerts
|

Abelhas (Hymenoptera, Apidae sensu lato) do Estado de Mato Grosso do Sul, Brasil

Abstract: ABSTRACT. Checklist of bees (Hymenoptera, Apidae sensu lato) from Mato Grosso do Sul state, Brazil. In this paper a current list of the bee species from Mato Grosso do Sul State, Brazil is presented and available in the online database of collections and reported in the literature, besides own collections held in diff erent localities in the state, encompassing diff erent vegetation types. The total number of bee species recorded for Mato Grosso do Sul, including morphospecies, is 386 species, distributed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…Therefore we were not able to point out an indicator species to monitor environmental changes. Lima & Silvestre (2017) cataloged 386 species of bees (Apidae s. lato) in Mato Grosso do Sul, with citation of some species of Meliponini also recorded in the present study, such as Paratrigona lineata, Tetragonia clavipes, Tetragonisca fiebrigi, Trigona hyalinata. In this context, this study presents four new occurrence records for the state of Mato Grosso do Sul, Frieseomelitta cf.…”
Section: Resultssupporting
confidence: 71%
“…Therefore we were not able to point out an indicator species to monitor environmental changes. Lima & Silvestre (2017) cataloged 386 species of bees (Apidae s. lato) in Mato Grosso do Sul, with citation of some species of Meliponini also recorded in the present study, such as Paratrigona lineata, Tetragonia clavipes, Tetragonisca fiebrigi, Trigona hyalinata. In this context, this study presents four new occurrence records for the state of Mato Grosso do Sul, Frieseomelitta cf.…”
Section: Resultssupporting
confidence: 71%
“…It may occur over the entire territory of Brazil (Silveira et al 2002). This species is currently known from Dourados, southern Mato Grosso do Sul (Henrique et al 2006, Lima andSilvestre 2017) and the Aporé-Sucuriú Complex, northern Mato Grosso do Sul (Aoki and Sigrist 2006), as well as in the south-central region of this state (Polatto et al 2014). All records are from areas of Cerrado or Cerrado-Atlantic forest transitions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Aoki et al (2012) reported it from the Amolar region in the Brazilian Pantanal (Fig. 1B, sample point 2) during an inventory in Eliezer Batista Private Reserve of Natural Heritage, but because no material was deposited in the state collection, this species went unreported by Lima and Silvestre (2017). Aoki et al (2012) observed H. velutina visiting only 1 plant species, Melochia pyramidata (Malvales, Malvaceae).…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, no Brasil, as estratégias para a conservação envolvem muitas ações, como os estudos taxonômicos que permitem conhecer as abelhas ocorrentes no país (Lima & Silvestre, 2017), o estabelecimento de legislações específicas (Koser et al, 2020), incentivos à criação das abelhas nativas (meliponicultura) (Carvalho et al, 2018) e a educação ambiental (Gomes et al, 2019;Bendini et al, 2020).…”
Section: Introductionunclassified